2011
DOI: 10.1371/journal.pone.0014566
|View full text |Cite
|
Sign up to set email alerts
|

Classifications for Cesarean Section: A Systematic Review

Abstract: BackgroundRising cesarean section (CS) rates are a major public health concern and cause worldwide debates. To propose and implement effective measures to reduce or increase CS rates where necessary requires an appropriate classification. Despite several existing CS classifications, there has not yet been a systematic review of these. This study aimed to 1) identify the main CS classifications used worldwide, 2) analyze advantages and deficiencies of each system.Methods and FindingsThree electronic databases w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
285
0
21

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(309 citation statements)
references
References 22 publications
3
285
0
21
Order By: Relevance
“…32 Hence, the variations found in our study (1.5-fold to 2-fold) are within the variability expected in multicenter studies. [30][31][32][33] Analysis of the TOCOS cohort led to three main results that could be used as a guide for prenatal counseling and for tailoring clinical surveillance in pregnancy ( Figures 3 and 4, Tables 3-5). The first result is confirmatory, on a much larger scale, of previously reported data.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…32 Hence, the variations found in our study (1.5-fold to 2-fold) are within the variability expected in multicenter studies. [30][31][32][33] Analysis of the TOCOS cohort led to three main results that could be used as a guide for prenatal counseling and for tailoring clinical surveillance in pregnancy ( Figures 3 and 4, Tables 3-5). The first result is confirmatory, on a much larger scale, of previously reported data.…”
Section: Discussionsupporting
confidence: 80%
“…[30][31][32] Cesarean section is a main marker of such differences, and the variability is enormous even within the same country. In a recent study in 593 US hospitals, rates varied almost 10-fold across hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…This classification would help understand the internal structure of these rates at individual health facilities and specific population groups. [11][12][13] Identifying the indications that lead to each group's contribution to the section rates would help in formulating guidelines to reduce rates. Within groups without compromising maternal and fetal welfare In 2015, the WHO issued an official statement concerning CS rates and promoting the use of the Robson classification as a tool for optimizing the CS rate at health care facilities.…”
Section: Introductionmentioning
confidence: 99%
“…7 In a systemic review conducted by WHO 2011, on various classification system it was found that a woman based classification in general and robsons classification in particular was best for auditing, analyzing and comparing CS rates across different setting and to implement effective strategies to optimize CS rate. 8 The aim of the study was to analyse the CS rate in various groups after classifying the deliveries in our institution according to Robson' ten group classifications. By this we aimed to identify specific group of women to be targeted to reduce CS rates.…”
mentioning
confidence: 99%